Teaching New English Vocabulary Items by Using Collocations in English as a Second Language classes at a Private University. - AL-NABHANI, MOHAMMED NABHAN (2021)
Teaching English vocabulary has not been given a sufficient attention in English as a second language classes. The perspectives on how to teach English words have altered since 1970s. As far as learning a second language is concerned, vocabulary is an essential component that helps learners to master the language. Thus, English vocabulary items must be treated as one of the main constituents of the English language and they should be taught intensively at the first levels. Several techniques, methods and approaches to teach vocabulary have appeared. One of these techniques is to teach words by using collocations.To teach vocabulary by using collocations is regarded as a comparatively new method. This research aims to test the effectiveness of teaching vocabulary by using collocations. This technique would lead to better results than introducing words by using the ordinary approaches like definitions, synonyms, antonyms and translation to the mother tongue. The research was done at a private university at the foundation department. The participants were 76 intermediate level students.The first chapter of this research includes a brief background about this research, problem statement, study’s goal, scope, importance of the investigation and research questions. The following chapter contains the review of the literature that discusses vocabulary in second language teaching, definitions and types of collocations. Chapter three includes the methodology of the research, materials, the chosen participants, the implemented procedures and the explanation of the statistical analysis. Theorists, teachers, researchers, and others involved in English as a Foreign Language (EFL) did not realize the role and significance of vocabulary in the acquisition of the English language. However, some scholars in linguistics have conducted some pedagogical materials and experimental studies that show the significance of vocabulary teaching and since then vocabulary teaching has been a valued issue in the field of teaching English. Most English language teachers think that the number of English words that learners know represents the knowledge of their vocabulary skills. However, some scholars indicate that the vocabulary knowledge includes other abilities. It refers to the student’s knowledge of the possible relation of words in a sentence, which word is convenient with which word. Combinality is a term that should be granted a special interest as it is a subject that English learners do not know how to deal with and they constantly produce incorrect collocational uses.